2015
DOI: 10.4103/2277-9175.153895
|View full text |Cite
|
Sign up to set email alerts
|

A histomorphometric study of the effect of doxycycline and erythromycin on bone formation in dental alveolar socket of rat

Abstract: Background:The aim of the present study was to evaluate whether subantimicrobial doses of doxycycline (DOX) and erythromycin (EM) used for the treatment of peri-implant osteolysis due to their anti-osteoclastogenesis can interfere with the osseous wound healing process in rat alveolar socket.Materials and Methods:Forty-five male Wistar rats had their first maxillary right molar extracted and were divided into three groups. DOX and EM at the doses of 5 mg/kg/day orally (p.o.) and 2 mg/kg/day intraperitoneally (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“… 28 Recently, low doses of orally administered DOX for 7 days have been found to enhance bone formation in the alveolar sockets of rats. 29 The bone matrix is composed primarily of type I collagen fibres, which are a marker of osteoblast differentiation. Bone strength depends on more than quantity and mainly depends on quality, which is characterised by the geometry and shape of bones, the microarchitecture of trabecular bone, bone turnover, and the presence of minerals and collagen.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Recently, low doses of orally administered DOX for 7 days have been found to enhance bone formation in the alveolar sockets of rats. 29 The bone matrix is composed primarily of type I collagen fibres, which are a marker of osteoblast differentiation. Bone strength depends on more than quantity and mainly depends on quality, which is characterised by the geometry and shape of bones, the microarchitecture of trabecular bone, bone turnover, and the presence of minerals and collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed in dogs, showed that doxycycline is able to reduce bone loss caused by endodontic peri radicular surgery 77 . However, another study showed that doxycycline does not improved the quantity and quality of tissue repair on bone in Wistar rats subjected to dental extraction and subsequently treated for 7 days on doxycycline and erythromycin 78 . This fact may be comprehended in this previous cited work, explaining that the rats were subjected to a short period of treatment with doxycycline (7 days) and the quantification was injured because of this short time of treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Erythromycin has bacteriostatic activities and is commonly prescribed for dental caries and dental plaque [ 55 , 56 , 58 ]. The most common microorganism that causes dental caries is Streptococcus mutans , which is highly sensitive to erythromycin [ 59 ].…”
Section: The Most Common Prescribed Antibioticsmentioning
confidence: 99%